2016
DOI: 10.1039/c6cy00498a
|View full text |Cite
|
Sign up to set email alerts
|

Towards biolubricant compatible vegetable oils by pore mouth hydrogenation with shape-selective Pt/ZSM-5 catalysts

Abstract: Pore mouth hydrogenation of vegetable oil with Pt/ZSM-5 is confirmed by the similar intermediately melting product selectivity for various crystal sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Trasarti et al reported the liquid-phase hydrogenation of SBO using copper catalysts, which exhibited unique properties for obtaining proper lubricants due to the selective hydrogenation of unsaturated linolenic (C18:3) and linoleic (C18:2) FAs to unsaturated oleic acid (C18:1), while saturated stearic acid (C18:0) was not formed. Although the advantages provided by Ni and Cu catalysts, such as low cost, easy removal from oils by filtration, and selectivity and some drawbacks such as the isomerization of natural cis to trans bonds during Ni-catalyzed hydrogenation and low activity at temperatures below 120 °C, noble metal catalysts (e.g., Pd, Pt, and Ru) are usually employed due to their high activity in small amounts at low temperature and the possibility of reuse. Each noble metal catalyst exhibits particular characteristics in selectivity, reactivity, and trans isomerization during hydrogenation of vegetal oils. It has been accepted that Pt catalysts produce the least amount of trans FA during hydrogenation, less than 8%, while conventional hydrogenation produces hydrogenated oils containing from 25 to 45% trans FAs.…”
Section: Modifications Of Vegetal Oils To Improve Oxidative Stabilitymentioning
confidence: 99%
“…Trasarti et al reported the liquid-phase hydrogenation of SBO using copper catalysts, which exhibited unique properties for obtaining proper lubricants due to the selective hydrogenation of unsaturated linolenic (C18:3) and linoleic (C18:2) FAs to unsaturated oleic acid (C18:1), while saturated stearic acid (C18:0) was not formed. Although the advantages provided by Ni and Cu catalysts, such as low cost, easy removal from oils by filtration, and selectivity and some drawbacks such as the isomerization of natural cis to trans bonds during Ni-catalyzed hydrogenation and low activity at temperatures below 120 °C, noble metal catalysts (e.g., Pd, Pt, and Ru) are usually employed due to their high activity in small amounts at low temperature and the possibility of reuse. Each noble metal catalyst exhibits particular characteristics in selectivity, reactivity, and trans isomerization during hydrogenation of vegetal oils. It has been accepted that Pt catalysts produce the least amount of trans FA during hydrogenation, less than 8%, while conventional hydrogenation produces hydrogenated oils containing from 25 to 45% trans FAs.…”
Section: Modifications Of Vegetal Oils To Improve Oxidative Stabilitymentioning
confidence: 99%
“…The alarming predictions of the rapid depletion of fossil‐fuel resources have inspired researchers to develop alternative technologies that exploit renewable energy sources . Many studies have focused on the conversion of lignocellulosic biomass and triglycerides into various platforms of value‐added chemicals .…”
Section: Introductionmentioning
confidence: 99%
“…2011) got better pour point and higher flash point when castor bean oil is chemically modified to form estolide ester by reacting ricinoleic acid of vegetable oil with saturated fatty acid [38]. Aelst et al (2016) partially hydrogenated soybean oil using Pt/ZSM-5 catalyst to improve oxidative stability and cold flow behaviour for biolubricants [39]. Borugadda and Goud (2014) improved thermal and oxidation stability of castor oil through epoxidation of castor oil forming fatty acid methyl esters of vegetable oil suitable as a biolubricant base stock [40].…”
Section: Higher Dispersancymentioning
confidence: 99%